Studi Hadis Arrujulu ‘Ala Dini Khalilihi (Kajian Tahlili) - Iga Diah Ipangga; Febriyeni Febriyeni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Choosing friends is the process of determining friends in everyday life, so that they make friends in accordance with Islamic religious law. This research seeks to determine the analysis of Naqd al-khariji and Naqd al-dakhili hadith arrujulu 'ala dini khalilihi. This research is qualitative in nature with a hadith science approach, such as the study of takhrij hadith and tahlili hadith on choosing friends. This research is included in library research by analyzing data descriptively and containing the analysis of the hadith arrujulu 'ala dini khalilihi, both from the analysis of the naqd al-khariji and naqd al-dakhili hadith. The results of the Naqd al-Khariji analysis research found the quality of Hasan hadith, it was proven that the narrator named Zuhair bin Muhammad had a shaduq assessment and there was 'illat in the path of Imam Ahmad bin Hanbal on page number 303, namely that the narrator named Mu'amil was not connected to the teacher. named Zuhair bin Muhammad causes this hadith to be dha'if, but there are other authentic narrations, so the quality of this hadith rises to a hasanic hadith. Meanwhile, the analysis of Naqd al-Dakhili includes an explanation of the contextualization of hadith which is able to provide an understanding of choosing friends based on their religion, one of which is friends who have pious and ascetic qualities, namely friends who are able to have a good influence and impact on other friends, as well as friends who are able to improve their quality. to always carry out the commands of Allah Ta'ala and abandon things that He has forbidden.